Treatment of trichomoniasis in pregnancy in sub-Saharan Africa does not appear to be associated with low birth weight or preterm birth - STRINGER, Elizabeth; READ, Jennifer S; HOFFMAN, Irving; VALENTINE, Megan; ABOUD, Said; GOLDENBERG, Robert L (South African medical journal, 2010)
To determine whether treatment of trichomoniasis increases the risk of prematurity. Sub-analysis of a randomised trial. We analysed data from HPTN trial of antenatal and intrapartum antibiotics to reduce chorioamnionitis-related perinatal HIV transmission. Pregnant women from four sites in Africa. Gestational age at the time of delivery or mean birth weight. Of 2,428 women-infant pairs included, 428 (18%) had trichomoniasis at enrolment. There were no differences in infant age or birth weight between women with or without trichomoniasis. By randomisation group, there were no differences in gestational age at birth or birth weight. Of the 428 women diagnosed with trichomoniasis, 365 (83%) received antibiotics and 63 (15%) did not. In analysis of actual use of antibiotics, women with trichomoniasis who received no treatment were more likely to deliver a preterm infant when the symphysis-fundal height was used to estimate gestational age (36% v. 23%; p=0.03), but not when the Ballard score was used (16% v. 21%; p=0.41). There were no differences in mean birth weight between groups. In pregnant women in sub-Saharan Africa, most of whom were HIV-infected, neither trichomoniasis nor its treatment appears to influence the risk of preterm birth or a low-birth-weight infant.